Quelques fêlures - Paquet, Suzanne (CV Photo)

(untitled) (Les Productions Ciel variable, 2002)
Isabelle Hayeur's work points as much to the idea of "realism" in photography as to that of authenticity of the landscape(s). These are linked issues, since the landscape is probably photography's last bastion of invisibility. The unknown, or unknowable, places that Hayeur fabricates by blending different sites into a single territory, a single tableau, are like faults or breaks that draw attention to the state of the non-places that surround us. Between the critical regard and the disturbance, Hayeur creates a unique attraction, difficult to name or qualify, to these disenchanted zones, which are as if dehumanized because they are too humanized.